The black swan the impact of the highly improbable - Taleb, Nassim Nicholas (New York Random House, 2010)
Examines the role of the unexpected, discussing why improbable events are not anticipated or understood properly, and how humans rationalize the black swan phenomenon to make it appear less random.
"Originally published in hardcover and in slightly different form in the United States ... by Random House in 2007."-T.p. verso.
Keywords: Uncertainty (Information theory) -Social aspects